Intercostal nerve cryoablation therapy for the repair of pectus excavatum: a systematic review - Eldredge, R. Scott; McMahon, Lisa (Frontiers in Surgery, 2023)
Introduction The minimally invasive repair of pectus excavatum (PE) is a painful procedure that can result in long-term hospitalization and opioid use. To mitigate the length of stay and opioid consumption, many different analgesia strategies have been implemented. The aim of this study is to review the use and patient outcomes of intercostal nerve cryoablation (INC) during PE repair reported in the literature. Methods An unfunded literature search using PubMed identifying articles discussing INC during PE repair from 1946 to 1 July 2023 was performed. Articles were included if they discussed patient outcomes with INC use during PE repair. Articles were excluded if they were reviews/meta-analyses, editorials, or not available in English. Each article was reviewed for bias by analyzing the study methods, data analysis, patient selection, and patient follow-up. Articles comparing outcomes of INC were considered significant if p-value was <0.05. Results A total of 34 articles were included in this review that described INC use during pectus repair. Most supported a decreased hospital length of stay and opioid use with INC. Overall, INC was associated with fewer short-term and long-term complications. However, the researchers reported varied results of total hospital costs with the use of INC. Conclusion The review was limited by a paucity of prospective studies and low number of patients who received INC. Despite this, the present data support INC as a safe and effective analgesic strategy during the repair of PE.